2010
DOI: 10.1677/erc-10-0083
|View full text |Cite
|
Sign up to set email alerts
|

Obesity hormone leptin induces growth and interferes with the cytotoxic effects of 5-fluorouracil in colorectal tumor stem cells

Abstract: The incidence of colon cancer has increased in developed countries, possibly due to sedentary lifestyle and high caloric diet. Experimental and epidemiological evidence suggests a link between colon cancer development and adipose tissue-derived circulating hormones. Leptin, a pluripotent cytokine secreted by adipocytes, is a key regulator of appetite and energy balance acting in the brain. On the other hand, leptin also controls many physiological and pathological processes in peripheral organs. Recent studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 61 publications
1
45
0
1
Order By: Relevance
“…Stem cells of the gastrointestinal tract may serve as a principal target of tumorigenic mutations due to their naturally long life-span and capacity for self-renewal. The concept of stem cell-driven tumorigenesis in CRC is supported by the identification and phenotypic characterization of a subpopulation of colon cancer cells capable of initiation and sustained reproduction of human colon carcinomas in immune-compromised mice (tumor-initiating cells or colorectal tumor stem cells) (27). Cancer stem cells (CSCs) form spheres when cultured in vitro in serum-free suspension cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells of the gastrointestinal tract may serve as a principal target of tumorigenic mutations due to their naturally long life-span and capacity for self-renewal. The concept of stem cell-driven tumorigenesis in CRC is supported by the identification and phenotypic characterization of a subpopulation of colon cancer cells capable of initiation and sustained reproduction of human colon carcinomas in immune-compromised mice (tumor-initiating cells or colorectal tumor stem cells) (27). Cancer stem cells (CSCs) form spheres when cultured in vitro in serum-free suspension cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, leptin increased the number and size of tumorspheres formed by HCT 116, LS174T and CaCo-2 cells. Bartucci et al reported that leptin enhances the formation of tumorsphere by increasing their size and number (27). Therefore, leptin may affect the growth and survival of CRC stem cells that promote colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Uważa się bowiem, że obserwowane zwiększenie liczby zachorowań na raka jelita grubego w krajach rozwiniętych może być wynikiem siedzącego trybu życia i zbyt dużej podaży kalorii [37]. Również liczba zgonów z powodu tej choroby w pewnym stopniu zależy od wskaźnika masy ciała (body mass index -BMI) [38].…”
Section: Aktywność Fizycznaunclassified
“…Similarly, leptin has been shown to increase colon cancer resistance to 5-FU treatment via activation of the PI3K/Akt pathway. 41 Mueller et al studied the effect of BEZ235 and irinotecan on HT-29 cells and showed that BEZ235 increased the effect of irinotecan. 42 This study indicates that inhibition of the PI3K/Akt/mTOR pathway can be combined with a …”
mentioning
confidence: 99%